Pengaruh Digital Marketing Melalui Media Sosial dan Website Terhadap Keputusan Konsumen dalam Membeli Mobil (Studi Kasus Showroom 57 Maju Motor) - Abdillah, Ridwan Nashir; Asiyah, Siti; Ramadhan, Tri Sugiarti (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The objective of this research is to investigate the influence of social media and websites influence car purchase decisions at Showroom 57 Maju Motor in Malang Regency. The study's respondents ranged in age from 17 to over 50 years old, with a total of 30 participants, consisting of 21 men and 9 women from various occupations, including civil servants, private employees, store workers, students, healthcare workers, housewives, and salespeople. The data were analyzed through multiple linear regression using SPSS 20. The results of data analysis in this study were obtained from data samples collected through questionnaires filled out by respondents at the 57 Maju Motor Showroom, Malang Regency using SPSS software with the results that social media and websites have a positive and significant influence on purchasing decisions both partially and simultaneously. The social media variable has a partial effect, with a significance level of less than 5% alpha (0.048 < 0.05), while the website variable also has a significance level below the probability threshold (0.006 < 0.05). Simultaneously, social media and websites collectively influence car purchase decisions, with a significance value of 0.001, which is lower than the 5% alpha threshold (0.001 < 0.05). Keywords: Social Media, Website, Car Purchase Decisions, Multiple Linear Regression.